Ethnicity in the City: Tatar Urban Youth Culture in Kazan, Tatarstan. (August 2016) - Friedli, Andrea
In this article, the city and the urban space shall be understood as a political platform, where identities and powers are bargained, and as a screen on which they are projected. In this context, I will reflect on the strategies of identity management 'from below' employed by Tatar young people in Kazan and on their attempt to build a 'Tatar urban youth culture'. These identity strategies are mainly oriented against the 'Russian other', a decadent consumerist West and an ignorant rural Tatar culture and their main issue is the 'repossessing' of Kazan and the Tatarisation of the city. Such strategies namely include the use of the Tatar language in predominantly Russophone public spheres, the introduction of Tatar folkloristic elements in music and fashion as well as the appeal to a (lost) Tatar urban culture associated with an enlightened approach to Islam and to the pre-revolutionary Tatar intelligentsia. Tatar youth scenes thus use ethnicity as a resource in the linguistic, religious, historic and cultural (re)appropriation of the urban space, which in turn has to be understood as a symbolic political act in a specific historical as well as 'glocal' context. Thus, this article can be seen as a contribution to a critical approach towards cosmopolitanism introducing alternative concepts to reflect relationships, norms and values in urban life.